2019
DOI: 10.1158/1055-9965.epi-18-0468
|View full text |Cite
|
Sign up to set email alerts
|

Can Dietary and Physical Activity Modifications Reduce Breast Density in Postmenopausal Women? The DAMA Study, a Randomized Intervention Trial in Italy

Abstract: A modification of dietary habits or an increase in PA in postmenopausal women may reduce MBD. Further studies are needed to confirm these findings for planning breast cancer preventive strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…We have previously shown that the overall annual MD change is − 1.0 cm 2 [15]. In contrast to overall MD, natural MD change is not strongly influenced by typical risk factors for breast cancer, except for BMI and physical activity, although results remain inconclusive for postmenopausal women [15,[22][23][24][25]. MD can however be decreased.…”
Section: Introductionmentioning
confidence: 92%
“…We have previously shown that the overall annual MD change is − 1.0 cm 2 [15]. In contrast to overall MD, natural MD change is not strongly influenced by typical risk factors for breast cancer, except for BMI and physical activity, although results remain inconclusive for postmenopausal women [15,[22][23][24][25]. MD can however be decreased.…”
Section: Introductionmentioning
confidence: 92%
“…At the study level, only one RCT [29] included in the review was judged to have a low risk of bias. Common issues included a lack of information about allocation concealment [31,33], participant retention of < 85% [30][31][32], the absence of 'intention to treat' analyses [31][32][33], and a lack of prospective registration on a public trials registry [30][31][32][33]. In addition, two RCTs only followed-up outcomes for 3-months, which limits our understanding of the long-term effectiveness of lifestyle interventions.…”
Section: Discussionmentioning
confidence: 99%
“…One study objectively measured physical activity via accelerometery [29], three studies employed self-report questionnaires [30,31,33], and one study used both objective (accelerometery) and self-report measures [32]. Data from one RCT were insufficient to pool [33]. A meta-analysis of the remaining four RCTs [29][30][31][32] consisting of 440 participants showed a statistically significant increase in physical activity in the intervention groups compared with controls (SMD 0.31, 95% CI 0.13 to 0.50; p = 0.001; low quality evidence).…”
Section: Physical Activitymentioning
confidence: 99%
See 2 more Smart Citations